Max Hering Torres y Nelson A. Rojas eds., Microhistorias de la transgresión (Bogotá: Universidad Nacional de Colombia, Universidad Cooperativa de Colombia, Universidad del Rosario, 2015), 465 pp. (2016)
COL0008334